Changes in lipid abundance are associated with disease progression and treatment response in chronic Trypanosoma cruzi infection - Juan Carlos Gabaldón-Figueira; Albert Ros-Lucas; Nieves Martínez-Peinado; Gavin Blackburn; Irene Losada-Galvan; Elizabeth Posada; Cristina Ballart; Elisa Escabia; Jordi Capellades; Oscar Yanes; María-Jesús Pinazo; Joaquim Gascón; et al. (Parasites & Vectors)
Abstract Background Chagas disease, caused by the parasite Trypanosoma cruzi, is a zoonosis that affects more than seven million people. Current limitations on the diagnosis of the disease hinder the prognosis of patients and the evaluation of treatment efficacy, slowing the development of new therapeutic options. The infection is known to disrupt several host metabolic pathways, providing an opportunity for the identification of biomarkers. Methods The metabolomic and lipidomic profiles of a cohort of symptomatic and asymptomatic patients with T. cruzi infection and a group of uninfected controls were analysed using liquid chromatography/mass spectrometry. Differences among all groups and changes before and after receiving anti-parasitic treatment across those with T. cruzi infection were explored. Results Three lipids were found to differentiate between symptomatic and asymptomatic participants: 10-hydroxydecanoic acid and phosphatidylethanolamines PE(18:0/20:4) and PE(18:1/20:4). Additionally, sphinganine, 4-hydroxysphinganine, hexadecasphinganine, and other sphingolipids showed post-treatment abundance similar to that in non-infected controls. Conclusions These molecules hold promise as potentially useful biomarkers for monitoring disease progression and treatment response in patients with chronic T. cruzi infection. Graphical Abstract